REVIEW: MENENTUKAN PERBANDINGAN JARI-JARI IONIK ATOM KECIL DENGAN ATOM BESAR (r/R) DAN SUDUT APIT (ÆŸ) PADA STRUKTUR KRISTAL TETRAHEDRON DENGAN TEORI MENELAUS - Irzaman Irzaman; Raden Silfia Epriyanti; Johan Iskandar; Ade Kurniawan; Aminullah Aminullah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Study of crystal structure of ceramic materials was one of chapters in Solid State Physics for undergraduate curriculum in Indonesia. Tetrahedron crystal structure was interesting to be reviewed in order to provide an understanding to the students for analyzing the ionic radius ratio of small and large atoms (r/R) as molecul composer in ceramic materials. Study of ratio on tetrahedron crystal structure (coordination number of 4) was more difficult than octahedron (coordination number of 6) as well as cubic structures (coordination number of 8), because on tetrahedron, small atoms bound four large ionic atoms which were located in three-dimensional space that causing the wedge angle (Éµ) became not perpendicular to each other. A review of tetrahedron crystal structure using mathematical physics analysis of Menelaus theorem resulted r/R ratio of 0.225 with wedge angle of 109.5o. Key words: crystal structure, ionic radius, Menelaus theorem, ratio of r/R, tetrahedron.